Record of Discussions 51st Meeting of National Development Council - Planning Commission (Planning Commission, 2005)
The National Development Council (NDC) held its 51st Meeting at Vigyan Bhavan, New Delhi on the 27th and 28th June, 2005 under the Chairmanship of Dr. Man Mohan Singh, Prime Minister and Chairman of the Council to consider the Mid-Term Appraisal of the Tenth Five Year Plan. The list of participants is appended. The decisions of the meeting, approved by the Prime Minister (circulated separately) have also been appended.
Government of India Planning Commission
Government of India Planning Commission